Thành phần hóa học và hoạt tính gây độc tế bào của loài kim giao núi đất (Nageia wallichiana) thu tại tỉnh Lâm Đồng. Phần 1. Các hợp chất diterpenoid - Liễu, Nguyễnq Thị; Ninh, Phạm Thị; Hoàng Anh, Nguyễn Thị; Thủy, Trịnh Thị; Lưu, Nguyễn Thị; Lộc, Trần Văn; Phòng, Đinh Thị; Phương Thảo, Trần Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2016)
From the ethyl acetate extract of Nageia wallichiana, collected in Lam Dong province, Vietnam four diterpenoids with the abietane skeleton and one nor-diterpene dilacton have been isolated. Their structures were elucidated by using combined spectroscopic methods as IR, MS and NMR. The cytotoxic activity of three of five compounds against 8 human cancer cell lines has been evaluated.  The nor-diterpene dilactone showed strong activity on all tested cancer cell lines. This is the first report on the chemical constituents and the cytotoxic activity of Nageia wallichiana. Keywords. Diterpenoids, nor-diterpene dilactone Nageia wallichiana, cytotoxicity